Method Fatwa Assembly of Indonesian Ulama About Covid-19 Vaccination Law: A Maqashid Sharia Analysis - Muhammad Ilyas Sembiring; Hafsah Hafsah; Ramadhan Syahmedi Siregar (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2022)
This study aims to find out the ijtihad procedure carried out by the MUI in producing fatwa Number 14 of 2021 concerning the covid-19 vaccination law, to find out the legal basis used in establishing the MUI fatwa on the covid-19 vaccination law, and to find out the MUI review in the use of Maqosyid Syariah in producing fatwa Number 14 of 2021 concerning covid-19 vaccination. This type of research is library research using secondary data sources in Fatwa document Number 14 of 2021 related to Covid-19 Vaccination. This research uses content analysis techniques (content analysis) to explore the contents or meanings contained in the documents for the ijtihad procedure carried out by the Indonesian Ulema Council in issuing legal products in the form of fatwas. From the results of this study, it can be concluded that the foundation of the Indonesian Ulema Council in issuing fatwas related to covid-19 vaccination is to use the term method (benefit analysis), or it can be called Maslahah al-Mursala. The legal basis used by the Indonesian Ulema Council in Fatwa Number 14 of 2021 is the Al-Quran, hadith, ijma, fiqh principles, and the opinions of salaf scholars. Maqasyid Syariah, one of the approach instruments used by MUI, is to adhere to Dharuriyat Hifz al-din (safeguarding religion) principles and Hifz al-nafs (safeguarding the soul)